Interactions Between the Entomopathogenic Fungi Beauveria bassiana (Ascomycota: Hypocreales) and the Aphid Parasitoid Diaeretiella rapae (Hymenoptera: Braconidae) on Myzus persicae (Hemiptera: Aphididae) - Martins, I. C. F. [UNESP]; Silva, R. J. [UNESP]; Alencar, J. R. D. C. C. [UNESP]; Silva, K. P. [UNESP]; Cividanes, F. J. [UNESP]; Duarte, R. T. [UNESP]; Agostini, L. T. [UNESP]; Polanczyk, R. A. [UNESP] (Entomological Soc Amer, 2014)
The interactions between the entomopathogenic fungus Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Ascomycota: Hypocreales) and the aphid parasitoid Diaeretiella rapae McIntoch (Hymenoptera: Braconidae) were evaluated under laboratory conditions. Nymphs of Myzus persicae Sulzer (Hemiptera: Aphididae) were first exposed to parasitoid females for 24 h and then 0, 24, and 48 h afterwards sprayed with a solution of B. bassiana. Likewise, aphids were also sprayed with B. bassiana and then exposed to parasitoids at 0, 24, and 48 h afterwards. Parasitism rate varied from 13 to 66.5%, and were signi_cantly lower in treatments where the two agents were exposed within a 0-24 h time interval compared with the control (without B. bassiana). Parasitoid emergence was negatively affected in treatments with B. bassiana spraying and subsequent exposure to D. rapae. Decreases in longevity of adult females of the D. rapae F1 generation were observed in treatments with B. bassiana spraying. The application of these two biological control agents can be used in combination on the control of M. persicae, wherein this use requires effective time management to avoid antagonistic interactions.
Keywords: Integrated pest management; Biological control; Natural enemy; Entomopathogen